2023
DOI: 10.3390/diagnostics13243683
|View full text |Cite
|
Sign up to set email alerts
|

ECMO in Myocardial Infarction-Associated Cardiogenic Shock: Blood Biomarkers as Predictors of Mortality

Thomas Senoner,
Benedikt Treml,
Robert Breitkopf
et al.

Abstract: Background: Veno-arterial extracorporeal membrane oxygenation (va-ECMO) can provide circulatory and respiratory support in patients with cardiogenic shock. The main aim of this work was to investigate the association of blood biomarkers with mortality in patients with myocardial infarction needing va-ECMO support. Methods: We retrospectively analyzed electronic medical charts from patients receiving va-ECMO support in the period from 2008 to 2021 at the Medical University Innsbruck, Department of Anesthesiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Various studies have reported different mortality rates of ECMO in patients with cardiogenic shock. Overall, the results have been virtually heterogeneous, and the in-hospital mortality rate ranged from 40% to 60% [ 22 , 23 , 24 , 25 , 26 , 27 ]. Recent clinical trials comparing the efficacy of VA-ECMO and optimal medical treatment demonstrated that using ECMO in patients with cardiogenic shock did not improve early and long-term mortality [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported different mortality rates of ECMO in patients with cardiogenic shock. Overall, the results have been virtually heterogeneous, and the in-hospital mortality rate ranged from 40% to 60% [ 22 , 23 , 24 , 25 , 26 , 27 ]. Recent clinical trials comparing the efficacy of VA-ECMO and optimal medical treatment demonstrated that using ECMO in patients with cardiogenic shock did not improve early and long-term mortality [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%